Pengaruh Karakteristik CEO Terhadap Earnings Management - Utami, Adhira; Rina Trisnawati (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to analyze the influence of CEO characteristics on Earnings Management in real estate and property companies listed on the Indonesia Stock Exchange during the period 2020-2023. The variables studied include CEO gender, CEO age, CEO tenure, CEO educational background, CEO work experience, and CEO narcissism. The data used in this study is secondary data obtained from the companies' annual reports. The sampling method employed in this study is purposive sampling, which resulted in 56 company data points over the period of 2020-2023. The data analysis technique used is multiple regression analysis. The results indicate that CEO gender significantly influences Earnings Management, with female CEOs tending to engage in lower earnings management practices. Additionally, CEO tenure also significantly affects Earnings Management. However, CEO age, educational background, work experience, and CEO narcissism did not significant effect on Earnings Management. This study has limitations in terms of the sector and period under consideration, and future research is recommended to broaden the scope and research period.